A scheme of correlation for frictional pressure drop in steam–water two-phase flow in helicoidal tubes. (17th February 2015) - Colombo, Marco; Colombo, Luigi P.M.; Cammi, Antonio; Ricotti, Marco E.
Abstract: In the nuclear field, helically coiled tube steam generators (SGs) are considered as a primary option for different nuclear reactor projects of Generation III+ and Generation IV. For their characteristics, in particular compactness of the component design, higher heat transfer rates and better capability to accommodate thermal expansion, they are especially attractive for small-medium modular reactors (SMRs) of Generation III+. In this paper, starting from two existing databases, a new correlation is developed for the determination of the two-phase frictional pressure drop. The experimental data cover the ranges 5–65 bar for the pressure, 200 to 800 kg/m 2  s for the mass flux and 0 to 1 for the quality. Two coil diameters have been considered, namely 0.292 m and 1.0 m. The coil diameter in particular is crucial for a correct estimation of the two-phase frictional pressure drop. Actually, no general correlation reliable in a wide range of coil geometries is available at the moment. Starting from the noteworthy correlation of Lockhart and Martinelli, corrective parameters are included to account for the effect of the centrifugal force, introduced by the helical geometry, and the system pressure. The correlation is developed with the aim to obtain a form of general validity, while keeping as low as possible the number of empirical coefficients involved. The average relative deviation between the correlation and the experimental data is about 12.9% on the whole database, which results the best among numerous literature correlations. In addition, the new correlation is characterized by an extended range of validity, in particular for the diameter of the coil. Highlights: A correlation for two-phase frictional pressure drops in helical pipes is proposed. The correlation is developed with experimental data from different coil geometries. Comparison with other correlations shows improvement of the accuracy. The correlation holds over an extended range of parameters. The scheme of correlation accounts for the essential effect of the coil diameter.